PERSEPSI PETANI TERHADAP PENGGUNAAN MESIN TETAS PADA PEMBIBITAN TERNAK AYAM BURAS (Kasus di Desa Utama Kecamatan Cijeungjing Kabupaten Ciamis) - Sudrajat Sudrajat (Universitas Galuh Ciamis, 2017)
This study aims to determine the perception of farmers on the use of the incubator in domestic poultry breeding. The data used in this study consisted of primary data and secondary data. The primary data obtained through interviews with domestic poultry livestock farmers use pre-prepared questionnaires, while secondary data obtained from the offices/institutions associated with the research. Respondent conducted a census of all members of the Prosperous Farmers Group, as many as 43 people who participated in the livestock reproductive technology application training organized domestic poultry in the village LPPM Galuh University in Utama Village, District of Cijeungjing District, Ciamis Regency. Perception of farmers on the use of the incubator in domestic poultry breeding nature of the innovation seen from the indicators are relative advantage, compatibility, complexity, triability, and observability. Data analysis was performed using analysis of the average score. The results showed that the perception of farmers on the use of the incubator in domestic poultry breeding included into the category quite well. Thus the technology incubator is unacceptable and likely to be adopted by livestock farmers free-range chicken.